2017
DOI: 10.1177/0300060517725660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypercortisolism on bone mineral density and bone metabolism: A potential protective effect of adrenocorticotropic hormone in patients with Cushing’s disease

Abstract: ObjectiveTo investigate the effects of Cushing’s disease (CD) and adrenal-dependent Cushing’s syndrome (ACS) on bone mineral density (BMD) and bone metabolism.MethodsData were retrospectively collected for 55 patients with hypercortisolism (CD, n = 34; ACS n = 21) from January 1997 to June 2014. BMD was examined in all patients, and bone turnover markers were tested in some patients. Healthy controls (n = 18) were also recruited.ResultsThe lumbar spine and femoral neck BMD were significantly lower in the ACS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
(23 reference statements)
3
20
0
1
Order By: Relevance
“…These effects may be protective against osteonecrosis [ 5 , 8 , 9 ]. The potential positive effects of ACTH-induced VEGF release on bone are clinically evident in patients with ACTH-producing pituitary Cushing disease; these patients have less BMD loss than those with adrenal Cushing syndrome (with suppressed ACTH levels) [ 21 , 22 ]. In addition, ACTH concentrations in patients with pituitary Cushing disease correlate with lumbar BMD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects may be protective against osteonecrosis [ 5 , 8 , 9 ]. The potential positive effects of ACTH-induced VEGF release on bone are clinically evident in patients with ACTH-producing pituitary Cushing disease; these patients have less BMD loss than those with adrenal Cushing syndrome (with suppressed ACTH levels) [ 21 , 22 ]. In addition, ACTH concentrations in patients with pituitary Cushing disease correlate with lumbar BMD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential positive effects of ACTH-induced VEGF release on bone are clinically evident in patients with ACTH-producing pituitary Cushing disease; these patients have less BMD loss than those with adrenal Cushing syndrome (with suppressed ACTH levels) [ 21 , 22 ]. In addition, ACTH concentrations in patients with pituitary Cushing disease correlate with lumbar BMD [ 22 ]. Moreover, due to feedback on the hypothalamic-pituitary-adrenal axis, patients with familial glucocorticoid deficiency with elevated ACTH levels have a higher BMD than age-matched controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…P1NP and procollagen carboxy‐terminal propeptide (P1CP) have also been studied in several studies, with contradictory results . In a retrospective study with 21 patients with CS, it was shown that osteocalcin is depressed; this applies also for PINP, whereas CTX is increased …”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to excess GCs in patients with hypercortisolism results in bone loss. According to the recent study, ACTH might be protective for lumbar bone mineral density in patients with Cushing's disease, indicating ACTH might have a protective effect on bone ( Guo et al, 2018 ). Moreover, familial glucocorticoid deficiency (FGD), or hereditary unresponsiveness to ACTH, is an autosomal recessive disorder resulting from resistance to the action of ACTH on the adrenal cortex ( Maharaj et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%